Understanding social media marketing activities in Western Balkans : empirical insights from Kosovo - Rrustemi, Visar (Array, 2021)
Digital marketing activities through social media are being developed extensively by firms in the Western Balkans region, therefore the purpose of this paper is to investigate the impact of social media marketing activities on increasing sales of SMEs in the Western Balkans, with special emphasis on those of Kosovo. Using a sample of 100 manufacturing SMEs, we have researched the impact of digital marketing activities which are carried out through social media, on increasing the sales or turnover of these SMEs. The achieved results were analyzed through probit regression. The results show that facebook is mostly used for business activities in these SMEs. Also, the analyzed SMEs give a lot of importance to the opinions and comments of consumers expressed on social media. They design their business policies based on the comments and opinions received from online consumers. This empirical research provides data on the implementation of social media marketing activities by SMEs in the Western Balkans region.